PLANT GROWTH REGULATORS AND SHADE ON EMERGENCE IN MACADAMIA NUT TREE - Berchol da Silva Garbelini, Renata Cristina [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, Joao Domingos [UNESP]; Camili, Elisangela Clarete; Berchol da Silva, Antonio Renan (Univ Federal Uberlandia, 2016)
This study aimed to evaluate the effect of plant growth regulators and shading on seed germination of macadamia nut trees. The experiment was conducted in a seedling production nursery of the company QueenNut Macadamia located in the Palmeiras Farm, Dois Corregos, Sao Paulo (SP) state, Brazil. The Treatments were T1: water (control) under a shading screen, T2: GA(4+7) + N-(phenylmethyl)-aminopurine (Promalin (R)) at 200 mL L-1 under a shading screen, T3: Promalin (R) at 400 mL L-1 under a shading screen, T4: gibberellic acid (GA(3)) + kinetin (Kt) + 3-indolebutyric acid (IBA) - Stimulate (R) at 5 mL kg(-1) seeds under a shading screen, T5: Stimulate (R) at 10 mL kg-1 of seeds under a shading screen, and T6: water (control) under no shading screen. Seeds were soaked in the solutions or in water containing plant growth regulators for 24 hours. Then, they were dried and sown in sand. 450 seeds were used for each treatment. The evaluations began from seedling emergence by counting the total number of seedlings per treatment. A high average of macadamia nut tree seedling emergence was obtained in the treatments GA(4+7) + N-(phenylmethyl)-aminopurine (Promalin (R)) 400 mL L-1 with Sombrite (R) (75.7%), GA(4+7) + N-(phenylmethyl)-aminopurine (Promalin (R)) 200 mL L-1 (72.6%) Sombrite (R) and water (control) without Sombrite (R) (71.5%).
Keywords: Macadamia integrifolia; Gibberellins; Cytikinins